Study of Marine Sand-Dwelling Dinoflagellate With Four New Records From the Central South Coast of Viet Nam (Bangladesh Journal of Plant Taxonomy, 2021)
In this study, marine sand samples were collected from the shallow intertidal zone of Nha Trang bay, Viet Nam. Taxonomic observations were conducted for the sanddwelling dinoflagellates using light, epifluorescent and scanning electron microscopy. Morphology characterizations of the four species namely, Amphidiniopsis hexagona, Thecadinium pseudokofoidii, Amphidinium herdmanii and Fukuyoa ruetzleri have been reported as new records for Vietnamese coastal waters. The genus Amphidiniopsis and Thecadinium are a new addition to the dinoflagellates flora of Viet Nam. Taxomomic descriptions and photographs of these species have been provided.Bangladesh J. Plant Taxon. 28(2): 367-378, 2021 (December)